An Analysis of Flouting Maxim in the Tall Girl Movie - Ni Kadek Misiantari; I Gusti Ayu Vina Widiadnya Putri; Ida Ayu Putri Gita Ardiantari (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
The aim of study deals with flouting maxim in a movie entitled Tall Girl. People in conversation can run smoothly if they follow the cooperative principle. Grice (1975) stated that a cooperative principle in which at the stage at when it occurs by receiving the purpose or direction exchange in which you are engaged. There are four maxims that make up the cooperative principle namely maxim of quality, maxim of quantity, maxim of relevance, maxim of manner. However, not all conversation runs smoothly, sometimes people are uncooperative while conveying the information, this case known as flouting maxim. This study discusses maxim that was flouted by the characters in the Tall Girl movie. This study focuses on analyzing the types of flouting maxim and the reason why the characters flouted the maxims in the Tall Girl movie. There are two theories used to analyze the data in this research. First, the theory of cooperative principle was proposed by Grice (1975) to analyze the type of floating maxim and the second theory from Leech (1983) to analyze the reason for the flouting maxim. The researcher used a descriptive qualitative method to describe the data to answer the problem of the study. The result of the study shows that there are 10 data of floating maxim in Tall Girl Movie. The aim of study deals with flouting maxim in a movie entitled Tall Girl. People in conversation can run smoothly if they follow the cooperative principle. Grice (1975) stated that a cooperative principle in which at the stage at when it occurs by receiving the purpose or direction exchange in which you are engaged. There are four maxims that make up the cooperative principle namely maxim of quality, maxim of quantity, maxim of relevance, maxim of manner. However, not all conversation runs smoothly, sometimes people are uncooperative while conveying the information, this case known as flouting maxim. This study discusses maxim that was flouted by the characters in the Tall Girl movie. This study focuses on analyzing the types of flouting maxim and the reason why the characters flouted the maxims in the Tall Girl movie. There are two theories used to analyze the data in this research. First, the theory of cooperative principle was proposed by Grice (1975) to analyze the type of floating maxim and the second theory from Leech (1983) to analyze the reason for the flouting maxim. The researcher used a descriptive qualitative method to describe the data to answer the problem of the study. The result of the study shows that there are 10 data of floating maxim in Tall Girl Movie.